Contribution of Principles of Governance on Effective Student Leadership in Public Universities in Kenya: A Comparative Study of Two Universities. - Okeyo, Washington; Scholastica, Ratanya (Advances in Social Sciences Research Journal, 2018)
Effective student leadership is considered as one of the major elements that guarantee sustainable development and success for student bodies. Good governance principles are significant ingredients for aspiring student leadership. The overall objective of this study was to determine the contribution of principles of governance on effective student leadership. This was a comparative study on the perspectives of principles of governance and leadership in Technical University of Mombasa and Pwani University. Descriptive survey research design was used and it was a census study on 48 student leaders. Structured closed ended questionnaires were used to collect data which was analyzed using both descriptive and inferential statistics through Statistical Package of Social Sciences version 23. The findings show that principles of governance had no relationship with student leadership (r=-0.581, p>0.05 for Technical University and r=-0.494, p>0.05) for Pwani University. However, one of the main findings of the study was that, legitimacy and direction did not have any relationship with effective student leadership for both Technical University and Pwani University as had been predicted. Another finding is that performance has a relationship with effective student leadership in Technical University in Technical University but not PUSA. The Universities should therefore, enhance training of student leaders on governance issues so as to develop effective student leadership.